Automobile Insurance in British Columbia: Autoplan Turns Thirty - Boivin, Denis W. (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2004)
This article describes the five components of “Autoplan” insurance. This is the commercial name given to the universal automobile insurance regime that has been available in British Columbia since March of 1974. The minimum package comes with the following coverage: (1) third party liability insurance; (2) statutory accident benefits; (3) uninsured motorist protection; (4) underinsured motorist protection; and (5) inverse liability insurance. In closing, the article describes the main restrictions placed on recovery that relate to the conduct of the insured person.